2016
DOI: 10.1007/s00213-016-4326-6
|View full text |Cite
|
Sign up to set email alerts
|

The association between habitual physical activity and cigarette cravings, and influence of smokers’ characteristics in disadvantaged smokers not ready to quit

Abstract: RationaleHabitual physical activity (PA) may have an important role in suppressing cigarette cravings. Systematic reviews show a strong acute effect of bouts of PA on reducing cigarette cravings, and it may be that these effects accumulate.ObjectivesThe aim was to investigate the relationship between habitual levels of PA and cigarette cravings in disadvantaged smokers not ready to quit by examining baseline cross-sectional data from the Exercise Assisted Reduction then Stop smoking study (EARS).MethodsA serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
0
10
0
1
Order By: Relevance
“…This study also addresses the recall bias in prior studies on physical activity and smoking urges. For example, Haasova et al [12] showed that more habitual MVPA minutes based on 7-day activity recall significantly correlated with decreased urge over the past 7 days in 98 smokers. The difference between results from this 7-day recall study and our analysis suggests that the prevalence of MVPA and granularity of data are important factors to consider in studies on physical activity and smoking urge.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also addresses the recall bias in prior studies on physical activity and smoking urges. For example, Haasova et al [12] showed that more habitual MVPA minutes based on 7-day activity recall significantly correlated with decreased urge over the past 7 days in 98 smokers. The difference between results from this 7-day recall study and our analysis suggests that the prevalence of MVPA and granularity of data are important factors to consider in studies on physical activity and smoking urge.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…Although there is insufficient evidence to recommend exercise as an aid for smoking cessation [7,9], previous meta-analyses suggested that acute bouts of exercise decrease urges, with activities at moderate to vigorous intensity having the greatest effect [10,11]. In addition, a study on active smokers found that a higher level of habitual MVPA was significantly associated with lower smoking urges [12]. However, this study used 7-day physical activity recall for assessing the levels of MVPA, leading to potential recall bias.…”
Section: Introductionmentioning
confidence: 99%
“…Dentre essas exposições, podemos citar: o uso de cinto de segurança e a forma de dirigir (SANTOS; ANDRADE; MARTINS, 2017); cuidados com o tabagismo (HAASOVA et al, 2016); o equilíbrio durante o consumo de bebidas alcoólicas (LA FAUCI et al, 2019); e a conscientização do controle da pressão arterial e do colesterol (PIO-ABREU; DRAGER, 2020; RODRIGUES, FERNANDES; DELGADO, 2020). No quarto componente, encontramos o domínio relacionamento social.…”
Section: Introductionunclassified
“…Regarding the scope of measurement, these studies only assessed acute effects of exercise on smoking urges, leaving uncertainty around the longitudinal association. Several studies exploring longer-term associations between PA and smoking behaviors [ 24 - 30 ] showed that exercise improved follow-up abstinence rates [ 24 , 26 , 27 ], increased time until next cigarette [ 30 ], led to reductions in smoking and cravings [ 25 , 29 ], and was associated with lower smoking intensity and reduced likelihood of smoking [ 28 ]. However, both smoking behaviors and PA measures in these studies were primarily obtained through self-assessment and recall, thus rendering these data susceptible to bias [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%